Nanotwinned alloys under high pressure - Wang, Melody M. (2025)
Nanotwinned alloys are of interest due to their high strength and ductility, but twin boundaries may not be stable under shear. Computational studies indicate that high hydrostatic pressure may suppress detwinning mechanisms. Here, we investigate the microstructural changes of nanotwinned-nanocrystalline copper-nickel and Inconel 725 alloys under quasi-hydrostatic pressures up to 50 gigapascals (GPa). The alloys are compressed in a diamond anvil cell. In-situ x-ray diffraction (XRD) and ex-situ transmission electron microscopy (TEM) were employed to monitor microstructural changes. Twin boundary deformation and grain growth occur at 11.4 GPa quasi-hydrostatic pressure in the copper-nickel alloy. Molecular dynamics (MD) simulations reveal that hydrostatic pressure causes elevated local shear stress at grain boundaries, which leads to atomic rearrangements. A superposition of hydrostatic and deviatoric pressures lead to partial dislocation mediated twin boundary migration. In contrast, the Inconel 725 alloy showed stable twin and grain boundaries up to a quasi-hydrostatic pressure of 12.7 GPa. Texture, high solid solution strengthening, and low stacking fault energy are hypothesized to the enhanced microstructural stability in Inconel 725.